The Effect Of Impurities On The Oxidation And Swelling Of Zinc Aluminum Alloys - H. E. Brauer (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1922)
PART I INTRODUCTION Among the zinc base alloys used for casting in metal moulds, particularly die casting, those alloys containing aluminum usually together with copper, are probably the most widely used. The reason lies in their desirable mechanical properties and the fluidity and absence of hot shortness which facilitate casting. Objection to the use of these alloys may bee raised on account of the rather frequent instances of failure of a type variously described as disintegration, exfoliation and intercrystalline corrosion. In all cases which have come to our knowledge where the conditions of service were known, failure has occurred upon exposure to moisture and heat varying from a hot moist atmosphere to high pressure steam. Moreover, the alloys described in all such cases contain impurities or alloying metals which the present authors have found to have enormous accelerating effects on intercrystalline oxidation in zinc-aluminum alloys. Thus Williams1 experimented with an alloy containing a large percentage of tin exposed in Cuba. Bauer2 reports failure of a boiler plug containing over 1 per cent. of impurities, doubtless lead for the most part, and Rawdon's3 examinations were made on an alloy containing 0.4 per cent. lead also exposed to the Tropics. No thorough investigation of the nature and cause of this type of failure has been made heretofore, so far as the authors are aware, although Rawdon correctly classified it as internal oxidation. We have, therefore, carried out this investigation in order to determine the exact nature of this phenomenon and the effect of other metals present as impurities or intentional additions in accelerating or-retarding it. In the appendix we include a considerable amount of data which may be valuable in selecting an alloy combining good physical properties with high resistance to oxidation.